(untitled) (LEARNing Landscapes, 2011)
The teenage brain is experiencing amazing transformations which set into motion unprecedented academic and emotional growth. As the brain is changing, technology works as a powerful influencer, sculpting and molding the mind. Computerbased instruction, in particular, is impacting the teenage brain as a motivator, tutor, and prolific source of information. Research synthesized from the fields of neuroscience, education, psychology, and technology inform and strengthen pedagogy for teaching secondary students.